2013
DOI: 10.1111/pbi.12133
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide discovery ofDNApolymorphisms in rice cultivars with contrasting drought and salinity stress response and their functional relevance

Abstract: SummaryNext-generation sequencing technologies provide opportunities to understand the genetic basis of phenotypic differences, such as abiotic stress response, even in the closely related cultivars via identification of large number of DNA polymorphisms. We performed wholegenome resequencing of three rice cultivars with contrasting responses to drought and salinity stress (sensitive IR64, drought-tolerant Nagina 22 and salinity-tolerant Pokkali). More than 356 million 90-bp paired-end reads were generated, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
123
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 59 publications
22
123
7
Order By: Relevance
“…The reads covered 91.65% of the reference genome. In agreement with previous reports of similar genome wide studies of other rice varieties 8.35% of the reads did not map to the reference genome [41,42]. Further analysis of the unmapped reads showed that the reads consisted of sequences which mapped to other Oryza sativa subspecies as has been reported previously [43].…”
Section: Discussionsupporting
confidence: 91%
“…The reads covered 91.65% of the reference genome. In agreement with previous reports of similar genome wide studies of other rice varieties 8.35% of the reads did not map to the reference genome [41,42]. Further analysis of the unmapped reads showed that the reads consisted of sequences which mapped to other Oryza sativa subspecies as has been reported previously [43].…”
Section: Discussionsupporting
confidence: 91%
“…Belaj et al (2003) reported that SSR markers show the highest level of polymorphism compared to RAPD and AFLP in olive. The same results were reported in various other studies where SSR markers were compared to other molecular markers (Jain et al, 2014). Therefore, SSRs have increasingly become the marker set of choice for genetic studies as they are abundant, highly polymorphic, codominant in nature, and genome-specific (Cuevas and Prom, 2013;Izzah et al, 2013).…”
Section: Introductionsupporting
confidence: 77%
“…Different stresses are constant threats to the field pea and the key to pea improvement programs is to have genetic variation for agronomically important traits within the parental lines that are used in crosses for maximizing the genetic gain (Taran et al, 2005). For this purpose, assessment of genetic diversity between germplasm/ varieties to utilize their protection, conservation, and registration is also used in breeding programs to provide the bulk of allelic variation in breeding material (Jain et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations